A three-dimensional finite element analysis of the stress distribution around the bone mini-implant interface based on the mini-implant angle of insertion, diameter, and length - K Sarika; Navaneethakrishnan Kurunji Kumaran; Sakthidaran Seralathan; Rathinavel Kumar Sathishkumar; Somasundaram Kanmani Preethi (Wolters Kluwer Medknow Publications, 2023)
Background: Temporary anchorage devices or mini implants have gained great attraction due to their capability to provide absolute anchorage, low cost, versatility, and can be loaded immediately after placement. Material and Methods: Finite element analysis was used to evaluate the distribution of stress at the bone mini implant interface based on different angles of insertion (30°, 45°, 60°, and 90°) mini implant diameter (1.3 mm, 1.6 mm, and 2 mm) and mini implant length (6 mm, 8 mm, and 10 mm). A retraction force of 2 N was applied. Results: Areas of maximum stress concentration were the head and neck of the mini implant and cortical bone around the mini implant. A very minimal amount of stress was found in the cancellous bone. The maximum stress found in the cortical bone was 5.1301 MPa and in the mini implant was 26.355 MPa with an angle of insertion of 30°, a 1.3 mm diameter, and a 6 mm length. The minimum stress found in the cortical bone was 1.4702 MPa and that in the mini implant was 5.3895 MPa with an angle of insertion of 90°, a 2 mm diameter, and a 10 mm length. Conclusion: For maximum stability, mini implants should be placed at a perpendicular angle of insertion with sufficient diameter and length.